2015
DOI: 10.18393/ejss.85620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of manure on organic carbon content and fractal dimensions of aggregates

Abstract: Article Info Received : 15.07.2014 Accepted : 21.11.2014 Effects of farmyard manure treatments on some soil structural parameters such as, aggregate stability (AS), geometric mean weight (GMWD) and mean weight (MWD) diameters, fragmentation (D) and mass (Dm) fractal dimensions, bulk density (BD) and organic C (OC) contents of aggregates were determined in a clay soil. Application of 67 Mg ha -1 farmyard manure to Vertic Haplustoll soil decreased AS 12.14% compared with the control. Manure treatment increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…On the other hand, the process of aggregation is supported by binding substances such as organic materials in general and organic acids in particular. Accordingly, various organic compounds and soil agglutinants, i.e., organic carbon (Table 4) and polysaccharides, are released in large amounts with the disintegration of FSP during the composting process, which transfer with the extract and facilitates aggregates formation and increases their stability (Annabiet al, 2011;Abd El-Halim and Lennartz, 2017;Bashir et al, 2016;Gülser et al, 2015;Sanjuán et al, 2001 andZhang et al, 2014). In addition, some organic matter sources are hydrophobic substances, which may also have increased the resistance of aggregates to slaking in water (Piccolo andMbagwu, 1999), the result is to increase the aggregate stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the process of aggregation is supported by binding substances such as organic materials in general and organic acids in particular. Accordingly, various organic compounds and soil agglutinants, i.e., organic carbon (Table 4) and polysaccharides, are released in large amounts with the disintegration of FSP during the composting process, which transfer with the extract and facilitates aggregates formation and increases their stability (Annabiet al, 2011;Abd El-Halim and Lennartz, 2017;Bashir et al, 2016;Gülser et al, 2015;Sanjuán et al, 2001 andZhang et al, 2014). In addition, some organic matter sources are hydrophobic substances, which may also have increased the resistance of aggregates to slaking in water (Piccolo andMbagwu, 1999), the result is to increase the aggregate stability.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent studies confirmed that soil improvement by addition of the organic materials reducesthe deterioration of geometric arrangement of soil aggregates (Bashir et al, 2016;Vidal-Beaudet et al, 2018;Farid et al, 2014;Tuo et al, 2017;Gülser et al, 2015 andZhang et al, 2014). An important positive relationship between soil organic carbon content and the increase of MWD was reported (Bashir et al, 2016;Gülser et al, 2015 andZhang et al, 2014). Soil organic carbon as a major binding agent is one of the important drivers of soil structure and stabilization process of their aggregates, hence improves the relative abundance of macroaggregates at the expense of other aggregates (Das et al, 2014;Kashif et al, 2015 andZhang et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Under this circumstances, using of organic manures such as compost, vermicompost, barnyard manures and biofertilizers is ecofriendly, easily avaliable and cost effective. It is reported that organic materials provide nutrient conversion of organic fertilizer and mineral fertilizer combination, protection of soil moisture, increasing of cation exchange capacity, improving soil physical and biological properties and providing control of erosion [6][7][8][9][10]. Among the organic materials peat often enchances aeration and water retention [11].…”
Section: Introductionmentioning
confidence: 99%
“…This method is considered to reduce carbon emissions and improve land use. It is an effective process that converts different organic solid waste materials into stable organic products applied in agriculture under optimized control conditions, thereby recycling waste materials (Rynk, 1992;Gülser et al, 2015). The compost of hazelnut husk waste should use as an organic material in soils after hazelnut harvesting.…”
Section: Introductionmentioning
confidence: 99%